2020
DOI: 10.1055/a-1239-4739
|View full text |Cite
|
Sign up to set email alerts
|

Flash glucose monitoring in diabetic dogs: a feasible method for evaluating glycemic control

Abstract: Zusammenfassung Gegenstand und Ziel Zur Reduktion der klinischen Symptome und zur Verhinderung von lebensbedrohlichen Komplikationen sind bei Hunden mit Diabetes mellitus individualisierte Behandlungsstrategien und regelmäßige Kontrollen notwendig. Sieben bis 14 Tage nach jeder Anpassung der Insulindosierung und danach monatlich wird das Erstellen von Blutglukose-Tagesprofilen empfohlen. Im Jahr 2016 wurde ein herstellerkalibriertes Gerät zur kontinuierlichen Glukosemessung als Alternative zur Messun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
3
11
0
1
Order By: Relevance
“…In contrast, the reduced sensor lifespan was less frequently reported by dog owners. These results are in agreement with those observed in previous studies in which the maximal duration of the FGMS (14 days) was reached in about 70% of cases [ 12 , 14 ]. In fact, the premature detachment of the sensor represents one of the most frequent complications in diabetic cats, with a median sensor wearing time ranging from 5 to 10 days [ 5 , 7 , 10 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, the reduced sensor lifespan was less frequently reported by dog owners. These results are in agreement with those observed in previous studies in which the maximal duration of the FGMS (14 days) was reached in about 70% of cases [ 12 , 14 ]. In fact, the premature detachment of the sensor represents one of the most frequent complications in diabetic cats, with a median sensor wearing time ranging from 5 to 10 days [ 5 , 7 , 10 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…In one study, the use of home blood glucose monitoring was associated with positive changes in the QoL parameters of cats and their owners and significant glycemic improvements [ 9 ]. In two recent studies, DPOs were asked to complete a questionnaire regarding their experience with the FGMS [ 10 , 11 ], while a third one has evaluated owner satisfaction with the use of an FGMS through a questionnaire containing 16 yes-or-no questions [ 12 ]. The FGMS was considered to be easy to use by DPOs and provided great satisfaction [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The recent advent of continuous monitoring systems for dogs allows a long-term monitoring of glucose concentrations up to 14 days and thus improved assessment. [14][15][16][17][18][19] The main objectives of this study were to investigate the relationship that is correlation between individual fructosamine-and mean glucose concentrations obtained by flash-glucose monitoring over one sensor wearing period in insulin treated diabetic dogs and to evaluate the reliability of fructosamine measurements to categorize glycaemic control.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that mild erythema at the site of the application of the FGMS was noted in one of the dogs. Dermatologic complications associated with the use of FreeStyle Libre have been reported in up to 80% and 18% of DD and cats, respectively [ 15 , 37 , 38 ] Allergic contact dermatitis, likely caused by the sensor’s built-in adhesive, is a known problem in human medicine and, in a retrospective study, it was observed in 3.8% of 1036 diabetic patients using FreeStyle Libre [ 39 ]. In a recent study, the incidence of device-related AEs was low in 3023 patients using Eversense XL [ 29 ].…”
Section: Discussionmentioning
confidence: 99%